THE DEVELOPMENT OF DORATOON-BASED LEARNING MEDIA INTEGRATED WITH LOCAL WISDOM FOR ELEMENTARY SCHOOL TEACHERS - Hana Lestari; Ima Rahmawati; Muzhir Ihsan; Ridwan Siskandar (PD PGMI se Indonesia, 2026)
The development of information and communication technology (ICT) has significantly transformed education, particularly in improving the quality of teaching and learning processes. However, most elementary school teachers in Pamijahan District, Bogor Regency, still face challenges in utilizing technology as an effective and contextual learning medium. This study aims to develop a Doratoon-based learning media integrated with local wisdom to enhance teachers’ competence in using ICT while promoting local cultural values in the learning process. The research employed a Research and Development (R&D) approach following a modified Borg and Gall model consisting of six stages: needs analysis, product design, initial development, expert validation, limited trial, and product revision. The results indicate that the developed Doratoon media achieved a high level of feasibility, with an average score of 92% from media experts and 88% from material experts. The limited trials revealed positive responses from teachers regarding ease of use, visual appeal, and contextual relevance. The Doratoon learning media incorporating local wisdom effectively supports teachers in designing interactive, engaging, and meaningful learning experiences while preserving Pamijahan’s cultural identity within elementary education.